Answer: (1) mean = 9.46; standard deviation = 3.74
Step-by-step explanation:
Answer:
5
Step-by-step explanation:
In order to solve this problem, we need to use Pythagorem Theorem (a^2+b^2=c^2)
When using the pythagorem theorem the hypoteneuse would be the c^2 and the two other sides would be a and b (the order doesn't matter).
So, our formula would be:
4^2+3^2=c^2
Simplifies into:
25=c^2
In order to remove the exponent 2, we would have to square root both sides by 2. After doing so, you get the answer 5.
Hope this helps! :)
Answer:
2x-5
Step-by-step explanation:
6x-5-4x
2x-5
rewrite the equation set = to 0.
x^2 + 5x - 8 = 0
The quadratic will not factor so you have to use the quadratic formula.
x = (-b + - sqrt(b^2 - 4ac))/2a
x = (5 + - sqrt(25 - 4* 1* -8))/2
x = (5 + - sqrt 57)/2
The x2is not the same as 2x. It is x^2. X tot he second power which makes the problem a quadratic equation. You cannot combine the terms x^2 and -5x because they so not have the same power.